Análise do desempenho térmico das residências construídas em paredes de concreto: um estudo de caso do conjunto habitacional Vivacidade-Tucuruí-PA - SANTOS, Marlon Braga dos (2022)
The present work seeks to evaluate the thermal performance of buildings constructed with reinforced concrete walls cast in situ at the Vivacidade housing estate in Tucuruí- PA, with the purpose of checking compliance with the Brazilian codes. We also performed comparative analysis between the sealing system used in the case study and the system traditionally used (masonry with ceramic blocks), providing subsidies for the choice of constructive solutions for projects in the region in the future. The chosen method consisted of the execution of three types of evaluation method recommended by NBR 15575:2013: simplified, analysis of thermal properties of the materials that make up the external walls and the roof of the houses at the Vivacidade housing estate, referencing them against the Brazilian code; informative, based on temperature and relative air humidity measurements in a representative housing unit, at a typical summer period; normative, performing computer simulation using Energy Plus software, which included one study case housing units and another housing unit with masonry walls.. Based on the informative and simplified methods, it was found that the housing unit thermal behavior was unsatisfactory, since this does not meet the minimum performance criteria stablished by the NBR 15575:2013. From the analysis of computer simulation results studied in great detail, it was clear that the values of internal and external temperature are numerically quite similar. This implies that the performance was satisfactory in both simulated cases in regards to the normal codes. At the end of the analysis of the three methods according to the performance codes, it can be concluded that the method to be regarded as conclusive is the normative method (performed by computer simulation). Furthermore, the sealing system does not exert a great influence on the thermal behavior, considering that the concrete walls have provided slightly higher thermal performance in relation to the system composed of ceramic blocks to seal. Therefore, it was concluded that the sealing system using concrete walls can be used in the study case region, as long as the projects are designed according to the climate conditions in the area.